Perceptually Linear Parameter Variations - Lindow, Norbert; Baum, Daniel; Hege, Hans-Christian (Computer graphics forum, 2012)
Most visual analysis tasks require interactive adjustment of parameter values. In general, a linear variation of a parameter, using for instance a GUI slider, changes the visual result in a perceptually non‐linear way. This hampers interactive adjustment of parameters, especially in regions where rapid perceptual changes occur. Selecting a good parameter value therefore remains a time‐consuming and often difficult task. We propose a novel technique to build a non‐linear function that maps a new parameter to the original parameter. By prefixing this function to the original parameter and using the new parameter as input, a linear relationship between input and visual feedback is obtained. To construct the non‐linear function, we measure the variation of the visual result using image metrics. Given a suitable perceptual image metric, perceptually linear image variations are achieved. We demonstrate the practical utility of our approach by implementing two common image metrics, a perceptual and a non‐perceptual one, and by applying the method to a few visual analysis tasks.